Resources, organizational capabilities, and competitive advantage: An application of the resource-based view in the Philippine franchising industry - Salamanca, Sheila Marie B. (Animo Repository, 2023)
Resource-based View is a canonical reference in strategic management, which focuses on the firm’s resources, organizational capabilities, and competitive advantage. Resource-based View defines the relationships among firm resources (Itami, 1987; Rumelt, 1984; Deirickx & Cool, 1989; Wernerfelt, 1984; Barney, 1991) and organizational capabilities (Andrews, 1971; Hofer & Schendel, 1978; Prahalad & Hamel, 1990; Ulrich & Hamel, 1991) that provide the critical sources of sustainable competitive advantage (Porter, 1980 & 1985; Ghemawat, 1986; Lieberman & Montgomery, 1988; Hamel & Prahalad, 1994). The primary goal of this research study was to determine the relationship among resources, organizational capabilities, and competitive advantage by applying the Resource-Based View to the Philippine franchising industry. The study, which used Hart’s (1995) framework, investigated the resources, organizational capabilities, and competitive advantages of the 185 franchisor members of Philippine Franchise Association and the Association of the Filipino Franchisors, Inc. (1) to determine the effect of intangible resources and tangible resources on organizational capabilities; (2) to examine the mediating effect of organizational capabilities between the franchisor firm’s resources and competitive advantage; (3) to determine which organizational capability affects the competitive advantage of the franchisor’s firm. Primary data were collected through a survey and were encoded and processed with the aid of the following statistical tools: Cronbach analysis, Confirmatory factor analysis, Fisher's exact test, Chi-square test, ANOVA, Linear Regression, and Mediation Analysis. Comprehensive descriptive statistics were presented to appreciate the characteristics of the respondents. The results showed, firstly, the significant resources that impact the organizational capabilities of the franchisor's firm. These were managerial skills, leadership, communication skills, franchisor-franchisee relationship, innovation, and physical capital. Secondly, the franchisor's firm's organizational capabilities mediated between intangible and tangible resources and its competitive advantages. The proportion of the mediation effects between intangible resources and competitive advantage was 33% while the mediation effects between tangible resources and competitive advantage was 20%. Lastly, the linear regression showed that all organizational capabilities, such as production, technology, distribution, procurement, design, and service, were predictors of competitive advantages’ metrics, such as cost leadership, differentiation, preemption, and future positioning of the franchisor's firm. Contribution of the research study to Resource-based View theory. This was the first empirical study that tested the Resource-based View theory to the Philippine franchising industry. Six out of ten resources impacted the organizational capabilities of the franchisor's firm. It was evident that organizational capabilities mediated between intangible and tangible resources, and competitive advantage. But there were only specific dimensions in which organizational capabilities predicted specific dimensions of competitive advantage, contrary to Hart's original declaration. Further, the instrument was a product of an independent research work which tested the reliability, content validity and construct validity of the RBV questionnaire. Future studies can focus on examining the impact of various resources on the dimensions of organizational capabilities. Moreover, future studies can determine the specific dimensions of organizational capabilities that mediate resources and competitive advantage. Since the resource-based view focuses on the relationship between resources, organizational capabilities, and competitive advantage, Future studies can focus on strategic resources and organizational capabilities that franchisors should strategically leverage for its competitive advantage. Finally, future studies can perform cluster analysis of franchisors using the dimensions of competitive advantage.